Interaksi Genetik x Lingkungan dan Variabilitas Genetik Galur Gandum Introduksi (Triticum aestivum L.) di Agroekosistem Tropika - Nur, Amin; Azrai, Muh.; Trikoesoemaningtyas, Trikoesoemaningtyas (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Thefocus of wheat research in Indonesia is to obtained newpotential wheat lines that are adapted to low-mid elevationand heat tolerant. This study was aimed to obtaininformation on the effect of interaction of season x line xlocation and genetic variability of wheat lines in tropicalagroecosystem. This study was conducted at the Seameo-Biotrop (<400 masl) and Indonesian Ornamental CropsResearch Institute-Cipanas (>1,000 masl) experimental fieldfor two seasons. The results showed that there was an effectof interaction of season x line x location on plant height,days to flowering, number of spikelet and floret, seed/headweight, rate of grain filling, yield, flag leaf width, stomatadensity, chlorophyll b, and leaf greenness. Meanwhileseveral characters were only influenced by the interaction ofline x location, they were yield component characters, ie.empty floret percentage, number of seed/ head, 1,000 seedweight, number of head/m2 and seed/plant weight. Sevencharacters were not influenced by interaction of neitherseason x line x environment nor line x location, they werenumber of productive tillers, head length, number ofseed/head, chlorophyll a, ratio of chlorophyll a/b, totalchlorophyll, and leaf thickness. The characters that havehigh heritability and wide genetic variability for the twoanalysis models were the number of spikelet.